Economic activities and traditional environmental management of the Buryats in the Russian part of the Selenga River basin - Yu. I. Drobyshev (Nomadic Civilization: Historical Research, 2023)
The article is devoted to the characteristics of the transformation of traditional environmental management among the Russian population of the Selenga River basin, which is part of the Baikal region, in the pre-revolutionary period and at the present time. The Buryats as representatives of the indigenous population inhabiting the steppe landscapes of the above-mentioned area were distinguished by a direct connection with nature and its biological resources. In the historical past, nomadic livestock raising and sedentary agriculture, as well as hunting and craft activities, which became important sources of livelihood, were sufficiently developed in the economic complex. Over a long period of residence in this region, the Buryats managed to accumulate valuable knowledge, acquire skills, and form traditions of adaptive environmental management. The article makes an attempt to analyze the traditional and modern environmental management of the Buryats, which has undergone a certain transformation and changes under the influence of ethno-ecological folk traditions and economic innovations of different periods of time.